Comparison of opioid‐related deaths by work‐related injury1. Issue 3 (9th November 2012) - Cheng, Melissa; Sauer, Brian; Johnson, Erin; Porucznik, Christina; Hegmann, Kurt
Abstract Objective To infer whether work‐related injuries may impact opioid‐related deaths. Methods Descriptive comparisons were done using data from the Utah Department of Health, the Office of Medical Examiners, and the Labor Commission on all Utah residents who died from opioid‐related deaths from 2008 to 2009. Results The majority of decedents (145 of 254, 57%) had at least one prior work‐related injury. Demographics were similar regardless of work injury status. However, lack of high school diploma (18% vs. 7%, P < 0.001), prevalence of mental illness (50% vs. 15%, P < 0.001), tobacco (61% vs. 12%, P < 0.001), alcohol (87% vs. 28%, P < 0.001), and illicit drug (50% vs. 4%, P < 0.001) use were all substantially higher than the background population. Conclusion A detailed history and screening for mental illness and substance abuse, including tobacco use, among injured workers may be helpful in avoiding potential opioid‐related deaths. Am. J. Ind. Med. 56:308–316, 2013. © 2012 Wiley Periodicals, Inc.